Investigation of turfgrass seed-coating: effects on storage, germination, and establishment - Mandal, Parul (My University, 2026)
Seed coating technology has the potential to improve seed germination, establishment, and storage, yet its effectiveness in turfgrass systems remains poorly understood and inconsistent. The objectives of this dissertation were to: 1) synthesize current knowledge of seed coating technologies in turfgrass (Chapter 1); 2) quantify short- and long-term storage temperature and condition effects on germination and seedling vigor of coated and noncoated cool-season seed (Chapters 2 and 3); and 3) evaluate the effects of seed coating, irrigation regimes, and soil types on turfgrass establishment in controlled and field environments (Chapters 4 and 5). In Chapter 1, the literature review revealed mixed results, with coating improving germination in some studies but providing minimal-to-no benefit in others, highlighting the need for targeted research in turfgrass systems. Chapter 2 evaluated coated and noncoated cool-season turfgrass seed stored for one month at 4, 22, 42, 62, and 82 °C. Germination remained high at 4 to 42 °C but declined at 62 °C and was <1% at 82 °C, indicating that heat stress was the primary cause of seed deterioration. Chapter 3 determined the effect of seed coating in different storage environments, including refrigerator, indoor, and non-insulated shed conditions for up to two years. Seed stored in the shed exhibited the greatest germination losses, whereas refrigerated and indoor storage maintained stable germination. Moving from storage to establishment, Chapter 4 evaluated the effects of seed coating, irrigation regimes, and soil types under controlled conditions. Seed coating had minimal and inconsistent effects, whereas irrigation frequency and soil type exerted a major influence on successful establishment. Chapter 5 extended this work to field conditions by evaluating seed coating and irrigation frequency under an automated rainout shelter. Seed coating did not improve emergence or turf cover; instead, optimal seeding timing and more frequent irrigation proved crucial for turfgrass establishment. Overall, this work demonstrates that seed coating alone was not a reliable strategy for improving turfgrass germination, establishment, or storage. Maintaining cool, stable storage conditions and ensuring adequate soil moisture through proper irrigation are far more critical for preserving seed viability and ensuring successful turfgrass establishment.
Keywords: Turfgrass; Seed coating; Seed storage; Seed germination; Seedling establishment; Irrigation